Signs of National Identity in the Graphic Design of Cypriot Print Advertisements - Zantides, Evripides (My University, 2020)
The current study seeks to identify signs of national identity through the design of commercial print advertisements in the Republic of Cyprus. Based on semiotic analysis of socio-cultural perspectives, the paper explores the relationship between images and texts, not only in terms of nonverbal and verbal messages, but also through typography and layout. In doing so, it also focuses on a case study of print advertisements designed for Laiko Kafekopteio (People’s Coffee). The research falls under the constructivist conception of national identity and explores the reading of advertisements as part of commercial nationalism in everyday life. While the findings of the study depict different cultural values and characteristics of the Cypriot national identity, they also portray how the socio-political development of the island is reflected in the design of the advertisements.
Keywords: national identity; signs; semiotics; advertising; graphic design; typography